Accounting Students Perceptions of Accountants Unethical Behavior - Ubaidillah, Moh (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2022)
This study aims to find out and obtain empirical evidence about the influence of ethical orientation, and the level of knowledge regarding accounting scandals on students' perceptions of the accountant's unethical behavior. The sampling in this study used the Purposive Sampling method which produced a sample of 77 S1 students of the Accounting Study Program at PGRI Madiun University who had completed the Auditing and Behavioral Accounting course. The data analysis method of this study uses Structural Equiation modeling (SEM) analysis with Partial Least Squares (PLS). The results showed that there are factors that influence students' perceptions of the accountant's unethical behavior. These results are all hypotheses accepted, namely the level of student knowledge about accounting scandals, student relativism and student idealism affecting students' perceptions of unethical behavior.